Profile of Micro, Small, and Medium Industrial Herbal Medicine Products in Sukoharjo Regency - Irmanida Batubara; Ninuk Purnaningsih; Titi Mawasti (Tropical Biopharmaca Research Center, IPB University, 2020)
Sukoharjo is one of the districts in Central Java that has a large number of herbal medicine entrepreneurs, including many small and medium industries. This small and medium industry needs to improve the quality of product safety. Therefore, this study aims to obtain the profile of small and medium industry herbal medicine products in Sukoharjo Regency. A total of 6 types of products (candy (1), mixture (3), extract (1), and tea (1)) were collected and the uniform weights, water content, organoleptic, hazardous metal content and microbiological safety were determined. The results showed that the product had fulfilled the water content, lead, cadmium, and arsenic content, and fulfilled the requirements of total plate count (TPC), coliform, and yeast mold. Product quality still needs to be improved in terms of uniformity of weight and packaging labels. The conclusion of this research is the profile of small and medium industry products in Sukoharjo Regency has met safety requirements but needs to be improved in quality.